Deposition processes and properties of coatings on steel fasteners — A review - Ping Ping Chung; James Wang; Yvonne Durandet (Friction)
Abstract Mechanical fastening is widely used in joining metals, particularly in automotive, aerospace, building and construction industries. However, the main concern on mechanical fastening is the issue of corrosion. An effective way to prolong the service life of steel fasteners is to apply protective coatings onto these components. This paper reviews and compares a few common coating deposition techniques, i.e., electroplating, hot-dip galvanizing, ion vapour deposition and mechanical plating, in terms of their characteristics. Compositional and microstructural properties including morphology and porosity, corrosion resistance performance and frictional performance of the coatings formed by each process are discussed in details. Hydrogen embrittlement, a premature failure often occurred on high strength steel fasteners, is also reviewed. The key results of recent studies of various metallic coatings on fasteners are presented to provide a fundamental understanding of the evolving topics, and the research gaps have been identified for further investigation.